Growth hormone and aging: a clinical review - Luis E. Fernández-Garza; Luis E. Fernández-Garza; Luis E. Fernández-Garza; Fernando Guillen-Silva; Fernando Guillen-Silva; Marcos A. Sotelo-Ibarra; Marcos A. Sotelo-Ibarra; Andrés Ely Domínguez-Mendoza; Silvia A. Barrera-Barrera; Hugo A. Barrera-Saldaña; Hugo A. Barrera-Saldaña; Hugo A. Barrera-Saldaña; et al. (Frontiers in Aging)
Aging is a complex biological process characterized by functional decline, reduced quality of life, and increased vulnerability to diseases such as type 2 diabetes, cardiovascular conditions, neurodegeneration, and cancer. Advances in medical technology have introduced the concept of aging therapies, with growth hormone (GH) and its primary mediator, insulin-like growth factor 1 (IGF-1), receiving considerable attention for their potential to counteract age-related physiological and metabolic changes. GH plays a multifaceted role in the human body, primarily influencing body composition by increasing muscle mass, reducing fat tissue, promoting bone formation, and regulating the metabolism of proteins, lipids, and glucose. Additional effects have been noted on endothelial function, cognitive performance, and circadian rhythms. This review examines the molecular mechanisms of GH in aging, its potential as an anti-aging therapy, and findings from clinical trials involving these hormones for this purpose. It also addresses the associated adverse effects, limitations, and controversies. While some studies report significant benefits, these therapies’ long-term safety and efficacy in promoting healthy aging remain uncertain, highlighting the need for further research.